EFISIENSI PENJUALAN TEMBAKAU VERGINIA BERDASARKAN BENTUK DAUN BASAH DAN DAUN KERING DI KECAMATAN SAKRA BARAT KABUPATEN LOMBOK TIMUR - Jamaluddin Jamaluddin; Mimi Cahayani (Fakultas Ekonomi Universitas Islam Al-Azhar, 2020)
To be able to determine the type of tobacco that provides maximum profit for farmers in Lita from the types of tobacco leaf forms that are sold, it is necessary to conduct a study entitled